The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/urbansci2030089
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Dwelling Units as Low-Income Housing: California’s Faustian Bargain

Abstract: In 2003, California allowed cities to count accessory dwelling units (ADU) towards low-income housing needs. Unless a city’s zoning code regulates the ADU’s maximum rent, occupancy income, and/or effective period, then the city may be unable to enforce low-income occupancy. After examining a stratified random sample of 57 low-, moderate-, and high-income cities, the high-income cities must proportionately accommodate more low-income needs than low-income cities. By contrast, low-income cities must quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The delivery of affordable housing through ADUs has been attempted in certain jurisdictions, particularly on the West Coast, in California, where high housing prices are a preeminent concern and ADUs are seen as one vehicle to addressing them by adding "hidden" density in a smart growth infill strategy (Wegmann and Chapple, 2014;Gabbe, 2019). Ramsey-Musolf (2018) exposes the way ADU policy has been used to satisfy low-income housing quotas across the state, but when investigated, the "lack of oversight and the unproven efficacy of ADUs as low-income housing means that California has low-income housing units that exist on paper but not in operation" (p. 2). In other words, municipalities were allowed to count potential ADUs toward meeting their goal of providing affordable housing units, but none of the cities' zoning bylaws regulated maximum rent, occupant income, for any length of time.…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of affordable housing through ADUs has been attempted in certain jurisdictions, particularly on the West Coast, in California, where high housing prices are a preeminent concern and ADUs are seen as one vehicle to addressing them by adding "hidden" density in a smart growth infill strategy (Wegmann and Chapple, 2014;Gabbe, 2019). Ramsey-Musolf (2018) exposes the way ADU policy has been used to satisfy low-income housing quotas across the state, but when investigated, the "lack of oversight and the unproven efficacy of ADUs as low-income housing means that California has low-income housing units that exist on paper but not in operation" (p. 2). In other words, municipalities were allowed to count potential ADUs toward meeting their goal of providing affordable housing units, but none of the cities' zoning bylaws regulated maximum rent, occupant income, for any length of time.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of ADUs in Vancouver, Seattle, and Portland rented for below-market rates (Chapple et al, 2017b). However, other studies reported that the rental costs of ADUs are similar to comparable apartments in multifamily developments (Ramsey-Musolf, 2018) and that the number of ADU applications was not associated with changes in the proportions of renters paying more than 50% of their income on housing (Pfeiffer, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are variations in the level of strictness considering ADU ordinances in localities, however, the regulatory instruments that the ordinances employ to intervene in ADU development remain similar. ADUs have been discretionary rather than ministerial, which means local governments require ADUs to meet strict development requirements, such as costly off-street parking, minimum lot size requirements, design standards, setbacks, height limits, and maximum unit size of ADUs (Chapple et al, 2020b ; Ramsey-Musolf 2018 ; Mukhija et al, 2014 ). Of the instruments, off-street parking requirements may particularly be an extensively restrictive regulation that prevents ADU development (Brinig and Garnett, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ADUs can house seniors, as they allow for independence while maintaining proximity to others and services that support their health, financial, and social needs (Pynoos et al, 2008; Lehning, 2011). They can also be a tool for housing vulnerable populations (Ramsey‐Musolf, 2018). While there is limited research to support a conclusion that ADUs have a positive impact in meeting the financial, familial, and social needs of many households, there is evidence to suggest that if encouraged and properly regulated, these units could both diversify the housing stock and contribute to a micro form of neighbourhood‐level “social mixing” (Mendez, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%